Model Hewan Coba pada Penelitian Diabetes - Husna, Fauzul; Suyatna, Franciscus D; Arozal, Wawaimuli; Purwaningsih, Erni H (Pharmaceutical Sciences and Research, 2019)
The animal model has been widely used and contributed vastly to the scientific research over the years. While it can be used as an alternate subject in a study, the selection of the animal is crucial to assess and investigate the influence of the environment and genes on the pathogenesis of a disease. Many factors contribute to the choosing of the animal. They can be ranged from the similarities with the modelled object, easily looked after with less expensive cost, good reproductive performance, ability to produce blood and tissue samples, well-known genetic composition, and the status of the disease can be explained. Research has been taking place to investigate and find the best approach to prevent and deal with diabetes mellitus (DM) and insulin resistance and its complications. It starts with an initial in vitro method and finished with a clinical trial. Similarly, a series of in vivo studies using the animal model has been done aiming at figuring out its conditions or diseases that are identical to that of humans. This article discusses a variety of animal models frequently used in DM research.